Biaxial testing of unbonded post-tensioned rocking bridge piers with external replacable dissipaters. - Marriott, Dion (Earthquake engineering & structural dynamics.)
The biaxial response of two bridge piers is experimentally investigated. A post-tensioned precast bridge pier with external replaceable mild steel dissipaters is tested under biaxial loading. The performance of the post-tensioned bridge pier is compared with a conventionally reinforced monolithic bridge pier. The experimental biaxial response is then compared with previous uniaxial experimental testing of identical bridge piers to understand the influence of biaxial loading, specifically concerning post-tensioned rocking sections. A 3-dimensional moment curvature and moment rotation analysis program is created to generate the monotonic section response of a conventional and post-tensioned bridge pier. After comparing the accuracy of the section analysis program to the experimental testing of the monolithic pier, the program is validated against the experimental testing of the post tensioned bridge pier. This section analysis program is then used in the calibration of a macro model to capture the entire cyclic response of the post-tensioned bridge pier. The macro model adopts multiple linear elastic compression only springs at the rocking interface, combined with non-linear inelastic springs for each of the mild steel dissipaters and returns encouraging results at both local and global levels. The paper concludes with a number of biaxial moment interaction design charts for monolithic and post tensioned bridge piers as a function of mechanical and geometric section properties. The design charts define the biaxial yield surface at nominal yield and at the design section capacity defined by one of three limit states.